Sectoral Innovation Systems for Agro-Industrial Transformation in Ethiopia: A Systematic Review of Integrated Agro-Industrial Parks and Global Value Chains (Ethiopian Journal of Economics, 2025)
Ethiopia’s agro-industrial transformation, driven by Integrated Agro-Industrial Parks (IAIPs), is central to agricultural modernization and economic growth. However, the role of Sectoral Innovation Systems (SIS) in supporting IAIPs, particularly in their integration into Global Value Chains (GVCs), remains underexplored. This systematic review examines the influence of SIS on Ethiopia’s agro-industrial transformation, with a focus on IAIPs and GVC participation. Based on 40 peer-reviewed studies published between 2000 and 2024, the review identifies how SIS can address key challenges, such as infrastructure deficits, market access, and innovation within IAIPs. Findings highlight that IAIPs contribute significantly to value addition, export growth, and agricultural commercialization, facilitating Ethiopia’s GVC integration. However,, barriers like weak institutional frameworks, limited technological adoption, and inefficiencies in logistics impede their full potential. To optimize IAIPs, the review stresses the importance of strategic investments in infrastructure, strengthening institutional frameworks, and fostering public-private collaborations. Additionally, policy interventions that prioritize technological innovation, particularly in digital agriculture, are critical for enhancing competitiveness. The study offers valuable insights for other developing countries aiming to utilize IAIPs and SIS for sustainable economic development.